A digital phoswich detector using time-over-threshold for depth of interaction in PET. (4th December 2020) - Prout, David L; Gu, Zheng; Shustef, Max; Chatziioannou, Arion F
Abstract: We present the performance of a digital phoswich positron emission tomography (PET) detector, composed by layers of pixilated scintillator arrays, read out by solid state light detectors and an application specific integrated circuit (ASIC). We investigated the use of integrated charge from the scintillation pulses along with time-over-threshold (ToT) to determine the layer of interaction (DOI) in the scintillator. Simulations were performed to assess the effectiveness of the ToT measurements for separating the scintillator events and identifying cross-layer-crystal-scatter (CLCS) events. These simulations indicate that ToT and charge integration from such a detector provide sufficient information to determine the layer of interaction. To demonstrate this in practice, we used a pair of prototype LYSO/BGO detectors. One detector consisted of a 19 × 19 array of 7 mm long LYSO crystals (1.36 mm pitch) coupled to a 16 × 16 array of 8 mm long BGO crystals (1.63 mm pitch). The other detector was similar except the LYSO crystal pitch was 1.63 mm. These detectors were coupled to an 8 × 8 multi-pixel photon counter mounted on a PETsys TOFPET2 ASIC. This high performance ASIC provided digital readout of the integrated charge and ToT from these detectors. We present a method to separate the events from the two scintillator layers using the ToT, and also investigate the performance of this detector. All the crystals within the proposed detector were clearly resolved, and the peak to valley ratio was 11.8 ± 4.0 and 10.1 ± 2.9 for the LYSO and BGO flood images. The measured energy resolution was 9.9% ± 1.3% and 28.5% ± 5.0% respectively for the LYSO and BGO crystals in the phoswich layers. The timing resolution between the LYSO–LYSO, LYSO–BGO and BGO–BGO coincidences was 468 ps, 1.33 ns and 2.14 ns respectively. Results show ToT can be used to identify the crystal layer where events occurred and also identify and reject the majority of CLCS events between layers.